The Effect of Seed Value Choice in an Incomplete Fuzzy Preference Relations Guided by Social Influence - ÇİÇEKLİ, SEVRA; Gürbüz, Tuncay (Springer International Publishing, 2022)
Nowadays, there is an enormous increase in alternatives almost in every area with the development of technology. Thus, it has become harder for a single decision maker (DM) to completely evaluate each alternative for a problem on hand. In group decision making (GDM) problems, each DM has a different effect on the final decision because of their background. Also, it has been observed that DM's judgments are affected by those of other DMs in the group. This is defined as social influence (SI). Social Influence Network (SIN) is useful especially when there is incomplete preference information. In this paper, a proposed model has been used to demonstrate the effect of seed value choice in completion process of missing fuzzy information given by DMs.
4th International Conference on Intelligent and Fuzzy Systems (INFUS)
▪ Book Series: Lecture Notes in Networks and Systems.
Keywords: Fuzzy Preference Relation; Social Influence Network; Group Decision Making